Genetic diversity and structure of domestic cavy (Cavia porcellus) populations from smallholder farms in southern Cameroon - Ayagirwe, Basengere; Meutchieye, Felix; Djikeng, Appolinaire; Skilton, Robert; Osama, Sarah; Manjeli, Yacouba (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2017)
Although domestic cavies are widely used in sub-Saharan Africa as a source of meat and income, there are only a few studies of their population structure and genetic relatedness. This seminal study was designed with the main objective to assess the genetic diversity and determine the population structure of cavy populations from Cameroon to guide the development of a cavy improvement program. Sixteen microsatellite markers were used to genotype 109 individuals from five cavy populations (Wouri, Moungo and Nkongsamba in the Littoral region, and MÃ©mÃ© and Fako in the Southwest region of Cameroon). Twelve markers worked in the five populations with a total of 17 alleles identified, with a range of 2.9 to 4.0 alleles per locus. Observed heterozygosity (from 0.022 to 0.277) among populations was lower than expected heterozygosity (from 0.42 to 0.54). Inbreeding rates between individuals of the populations and between individuals in each population were 59.3% and 57.2%, respectively, against a moderate differentiation rate of 4.9%. All the tested loci deviated from Hardy-Weinberg equilibrium, except for locus 3. Genetic distances between populations were small (from 0.008 to 0.277), with a high rate of variability among individuals within each population (54.4%). Three distinct genetic groups were structured. This study has shown that microsatellites are useful for the genetic characterization of cavy populations in Cameroon and that the populations investigated have sufficient genetic diversity that can be used to be deployed as a basis for weight, prolificacy and disease resistance improvement. The genetic of diversity in Southern Cameroon is wide and constitute an opportunity for cavy breeding program.Â